Developing an entrepreneurial mindset among engineering students: encouraging entrepreneurship into engineering education - João, Isabel (2021)
It is unquestionable the role of entrepreneurship as a driver of innovation and economic development. The world is dynamically changing and intensively interconnected carrying new challenges and opportunities to the new generation of engineers working in a world where innovation will continue to evolve very quickly. This paper addresses the need to train engineering students to be entrepreneurial engineers considering the global challenges and the role that higher education institutions should play in developing an entrepreneurial mindset among engineering students. The paper presents and discusses the results of a survey carried out in a Portuguese engineering school with the goal of investigate students' entrepreneurial mindsets. The main objective is to understand the extent by which entrepreneurship is addressed in students' engineering programs as well as students' perceptions of their entrepreneurial related skills and the reasons that would lead the students to start or not start a business as well as their perception of the ability to immediately start a business. The results of the study are critically analysed in light of the challenges and opportunities facing future engineers. The work, although limited to a specific context is a valuable starting point for additional research and for the implementation of faculty strategies to improve entrepreneurship education.